Nonabelianization of Higgs bundles - Hitchin, Nigel J.; Schaposnik, Laura P. (Journal of differential geometry, 2014)
We consider the integrable system on the moduli space of Higgs bundles restricted to the subvariety corresponding to representations of a surface group into certain noncompact real forms, and in doing so encounter as the fiber moduli spaces of rank 222 bundles on a spectral curve. This contrasts with the general case where the fiber is an abelian variety.